2016
DOI: 10.1002/bdra.23532
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a teratogenic risk in the offspring of health personnel exposed to ionizing radiation?!

Abstract: Background: The evidence concerning safety of occupational exposure to ionizing radiation on teratogenic effects mainly relies on animal models, disaster epidemiology and experience in cancer etiology. Following an explorative result on maternal exposure in medical occupations we conducted a feasibility study, addressing congenital anomalies (CA) in the offspring of health workers potentially exposed to radiation. Methods: In a prospective follow-up study, we enrolled women, identified by mandatory registratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Excessive radiation will affect reproductive function, resulting in infertility, exposure during pregnancy will also cause embryo deformity, abortion, and other adverse outcomes. 1 , 2 The epidemiological results of the Chernobyl accident found that long-term low-dose radiation increased the risk of infertility or postpartum anemia among women, 3 cohort study in high background radiation area found long-term low dose exposure to reduce male sperm motility. 4 These radiation–induced reproductive health problems plague scientific research workers, and it is urgent to find appropriate radiation protection agents and explore its biological mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive radiation will affect reproductive function, resulting in infertility, exposure during pregnancy will also cause embryo deformity, abortion, and other adverse outcomes. 1 , 2 The epidemiological results of the Chernobyl accident found that long-term low-dose radiation increased the risk of infertility or postpartum anemia among women, 3 cohort study in high background radiation area found long-term low dose exposure to reduce male sperm motility. 4 These radiation–induced reproductive health problems plague scientific research workers, and it is urgent to find appropriate radiation protection agents and explore its biological mechanism.…”
Section: Introductionmentioning
confidence: 99%